Pengaruh Citra Merek, Kualitas Produk dan Word Of Mouth Terhadap Keputusan Pembelian - Valerie Rahmawati; Beny Witjaksono (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
The growing fashion trend is caused by the economy which leads to intense competition from several well-known international fashion products, one of which is Charles & Keith. is a fashion product from Singapore whose target market is Asia, one of which is Indonesia. This product has succeeded in capturing the hearts of Indonesian consumers, especially women of reproductive age, namely the range of 17-35 years. This study aims to determine the effect of brand image, product quality and word of mouth variables on purchasing decisions for Charles & Keith bags. The sampling technique in this research is a non-probability sample with a total sample of 100 respondents. The data analysis technique in this study was using SPSS (Statistical Program For Social Science) version 27.0. The results of this study indicate that brand image has a positive effect on purchase satisfaction, product quality has a positive effect on purchasing decisions and word of mouth has a positive effect on purchasing decisions and together brand image, product quality and word of mouth have a positive effect on purchasing decisions on Charles & Keith consumers